The complete mitochondrial genome of the Oriental sea slug: Chromodoris orientalis (Nudibranchia, Chromodorididae). Issue 2 (3rd July 2018) - Yu, Cheol; Kim, Hana; Kim, Hyung June; Jung, Yun-Hwan
Abstract: The mitogenome sequence of sea slug, Chromodoris orientalis (Nudibranchia, Chromodorididae), has been decoded for the first time by coverage genome sequencing method. The overall base composition of C. orientalis mitogenome is 30.5% for A, 14.7% for C, 18.0% for G and 36.9% for T, and has low GC content 32.6%. The assembled mitogenome, consisting of 14, 266 bp, has unique 13 protein-coding genes, 22 transfer RNAs, and two ribosomal RNAs genes. The C. orientalis mitogenome has the common mitogenome gene order and feature of Nudipleura (a clade of sea slugs and sea snails). The complete mitogenome of C. orientalis provides essential and important DNA molecular data for further phylogenetic and evolutionary analysis for sea slugs and sea snails.